2022
DOI: 10.3389/fphys.2022.921657
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of Tactile Foraging Behavior in Pekin and Muscovy Ducks

Abstract: Ducks have developed a variety of foraging strategies that utilize touch sensitive bills to match their ecological niche within wetlands. These techniques include diving, sieving, dabbling, and grazing. Ducks exhibiting tactile specialization in foraging outperform visual and non-tactile foraging ducks in behavioral experiments and have a higher percentage of light-touch mechanoreceptor neurons expressing Piezo2 in the trigeminal ganglia. Belonging to two different tribes of Anseriformes, the well-studied tact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Avian Meissner corpuscles are structurally and functionally similar to their mammalian counterparts. Meissner corpuscles endow humans with the remarkable ability to manipulate objects and tools, facilitate sensorimotor control in mice, and enable tactile specialist birds to carry out a multitude of foraging behaviors (2,8,(25)(26)(27). While this manuscript was finalized, a preprint study reported the 3D architecture of the mouse Meissner corpuscle by FIB-SEM, which, together with earlier literature, permits a detailed comparison with the avian structure (28).…”
Section: Discussionmentioning
confidence: 88%
“…Avian Meissner corpuscles are structurally and functionally similar to their mammalian counterparts. Meissner corpuscles endow humans with the remarkable ability to manipulate objects and tools, facilitate sensorimotor control in mice, and enable tactile specialist birds to carry out a multitude of foraging behaviors (2,8,(25)(26)(27). While this manuscript was finalized, a preprint study reported the 3D architecture of the mouse Meissner corpuscle by FIB-SEM, which, together with earlier literature, permits a detailed comparison with the avian structure (28).…”
Section: Discussionmentioning
confidence: 88%
“…The copyright holder for this preprint (which this version posted April 6, 2023. ; https://doi.org/10.1101/2023.04.05.535701 doi: bioRxiv preprint Avian Meissner corpuscles are structurally and functionally similar to their mammalian counterparts. Meissner corpuscles endow humans with the remarkable ability to manipulate objects and tools, and enable tactile specialist birds to carry out a multitude of foraging behaviors 5,7,[22][23][24][25] . Whether mammalian LCs are mechanosensitive remains to be determined, but appears likely given that dissociated murine Schwann cells are mechanosensitive in culture 10,11 .…”
Section: Discussionmentioning
confidence: 99%
“…West et al (2022) described a significant difference in foraging behaviour between waterfowl species with Domestic ducks almost exclusively using a 'deep dabbling' behaviour when foraging, that involved fully submerging the bill and vigorously churning the water around them, whereas Muscovy ducks shifted to a 'surface dabbling' behaviour, skimming the surface of the water and producing very little water movement. Muscovy ducks are performing much less foraging by dabbling compared to grazing (West et al, 2022). As an example, Downs et al (2017) described that Muscovy ducks were spending only 1.4% of their time foraging by dabbling or probing in soil compared to 25% foraging by grazing or gleaning from the ground.…”
Section: Species-specific Issuesmentioning
confidence: 99%
“…Domestic ducks make use of water for foraging, feeding, drinking, exploration, even without prior experience (Donkin, 1989;Heyn et al, 2006;Liste et al, 2012a;Downs et al, 2017), just like their wild ancestors (see Section 3.1.1). West et al (2022) described a significant difference in foraging behaviour between waterfowl species with Domestic ducks almost exclusively using a 'deep dabbling' behaviour when foraging, that involved fully submerging the bill and vigorously churning the water around them, whereas Muscovy ducks shifted to a 'surface dabbling' behaviour, skimming the surface of the water and producing very little water movement. Muscovy ducks are performing much less foraging by dabbling compared to grazing (West et al, 2022).…”
Section: Species-specific Issuesmentioning
confidence: 99%